Análise da cadeia de valor do tabaco: o caso dos produtores da região Sudoeste do Estado do Paraná - Paeze, Andrea Marize Weschenfelder (2022)
The aim of this study it to analyze the value of tobacco in the Southwest region of Paraná State. The research method was divided in two stages: the first stage was of qualitative exploratory nature and the second stage was of descriptive nature. The information about the populational parameters were obtained through a census involving the complete enumeration of the research elements, it was composed by two hundred forty-five tobacco producers distributed in the twenty-eight cities of the Southwest region of Paraná State. With the data obtained in the semi-structured script and questionnaires, it was elaborated a specific analysis of the characteristics of value chain of tobacco contained in this territory. The results of the study have identified how the competitivity of the tobacco value chain in the region of the research is structured. The resultant information has facilitated the understanding of intervening factors in the tobacco chain and identified perspectives to improve the integration performance between sustainability matters and the economy to perpetuate the production of the region. It was concluded that correlating the competitivity variables and the stakeholders of the tobacco chain it is possible to reflect upon the perspectives for the future of the chain in question and seek to understand the role of tobacco in the production units as well as its importance in the household income.